Development Of A Rapid Test For Toxocariasis Using Recombinant Toxocara Cati Tes-120 Protein - Tan Farrizam, Siti Naqiuyah (2020)
Toxocariasis is a neglected zoonotic disease with worldwide distribution and has been shown to be especially prevalent among children from socio-economically disadvantaged populations. The causative agents are Toxocara canis and Toxocara cati in which the definitive hosts are dogs and cats, respectively. Although it is acknowledged that human toxocariasis is caused by both T. canis and T. cati, however, the importance of T. cati as a zoonotic agent of the disease has been under-recognized since T. cati TES is rarely used for Toxocara serodiagnosis and T. canis TES antigens are generally thought to be able to detect infections by both species. Thus, it is highly likely that some cases of T. cati infection may be missed by tests using only T. canis antigen. Therefore, it is an urgent need for the development of diagnostic tools that use both T. cati and T. canis recombinant antigens to enable detection of infections caused by both species. Previously, a T. cati recombinant protein TES-120 was successfully produced and cloned into a pGEX-4T-1 expression vector which showed good diagnostic potential in western blot. However, the yield was low and unsuitable for rapid test development. In this study, the T. cati DNA insert was cloned into a pET32 expression vector and two short peptides tagged variants [five residues each of aspartic acid (D) and lysine(K)] were designed to increase the chances of obtaining a good yield of the soluble recombinant protein. All three variants namely TES-120 cati/pET32a, TES-120 5D cati/pET32a, and TES-120 5K cati/pET32a were expressed and purified.